What is the most effective antecedent for developing entrepreneurial intention among Muslim youth in Indonesia? - Gunawan Baharuddin; Asmak Ab Rahman (Entrepreneurial Business and Economics Review (EBER), 2021)
Objective: The objective of the article is to examine the dominant antecedent (characteristic) for youth in Indonesia to become entrepreneurs, by using the theory of planned behaviour (TPB) model. Research Design & Methods: This work is a quantitative study with a deductive approach. It was conducted by surveying 727 undergraduate students from universities in Indonesia to measure both indicators for every construct (analysis factors) and correlation effects on other constructs (path analysis). All data obtained were analysed through partial least square structural equation modelling (PLS-SEM). Findings: Among the three exogenous driver constructs, Subjective Norms has the strongest effect on Intention (0.152), followed by Perceived Behavioural Control (0.040) and Personal Attitude (0.011). Implications & Recommendations: Knowing the potential character of youth who become entrepreneurs enables policymakers to effectively plan targeted programs and policies. This article suggests several recommendations that focus on support from surrounding people such family, friends, and role models, who could approve young people's decisions to start own businesses.Contribution & Value Added: This research supports and strengthens the work of several researchers on the cultural and value factors that influence intentions with the additional element of religious values and virtues.
Keywords: G41; L26; O15; 330; entrepreneurship; intention; youth; Theory of Planned Behaviour